Part II. Comparison of Neurodevelopmental Outcomes Between Normothermic and Hypothermic Pediatric Cardiopulmonary Bypass - Hannon, Claire E.; Osman, Zachary; Grant, Cathy; Chung, Emma M. L.; Corno, Antonio F. (Frontiers in Pediatrics, 2019)
Objectives In the previous study we demonstrated that normothermic cardiopulmonary bypass (N-CPB, ≥35°C) provided better early clinical outcomes compared to mild/moderate hypothermic cardiopulmonary bypass (H-CPB, 28-34°C) for congenital heart surgery. In this follow-up study we compare early neurodevelopmental outcomes 2-3 years post-surgery. Methods In this retrospective, non-randomised observational study, the medical notes of children from our previous cohort were reviewed after 2-3 years. Demographic and neurodevelopmental outcomes were tabulated to enable blinded statistical analysis comparing outcomes between N-CPB and H-CPB surgery for congenital heart defects. Multivariate logistic regression models were developed to identify any differences in outcomes after adjustment for confounders. Results Ninety-five children who underwent H-CPB (n=50) or N-CPB (n=45) were included. The proportions of patients with one or more adverse neurodevelopmental outcomes 2-3 years later were 14/50 (28.0%) in the H-CPB group and 11/45 (24.4%) in N-CPB, which was not significantly different between groups (p=0.47). The two CPB groups were balanced for demographic and surgical risk factors, with the exception of genetic conditions. A higher incidence of H-CPB patients acquired learning difficulties (23.1% compared to 2.56% for N-CPB (p=0.014)) and neurological deficits (30.8% compared to 7.69% for N-CPB (p=0.019)), but these differences were not robust to adjustment for genetic syndromes. Conclusions Our study did not reveal any significant differences in early neurodevelopmental outcomes between H-CPB or N-CPB surgery for congenital heart defects. The most important factor in predicting outcomes was, as expected, the presence of a genetic syndrome. We found no evidence that CPB temperature affects early neurodevelopmental outcomes.